(untitled) (Engineering Review, 2023)
In precast building construction, some beams are designed to support one or several concentrated loads resulting from the reactions of the attached cross beams. Consequently, the pocket beams without or with dapped ends may represent one of the innovative solutions to constitute the joints between the two attached members. In the present research work, the behaviour of dapped end beams that included rectangular opening loaded with in-plane force, have been investigated. Several detailing have been proposed, in addition the vertical stirrups, to improve the strength of the opening region including the use of steel fibre concrete (SFC),Configuration of the inclined crossed bars, jacketing with steel plates and the composite section technique with two arrangements of the reinforcement of the dapped end . Ten specimens have been tested under gradually increased vertical static loading. The tested specimens are categorized into two sets based on the configuration of dapped end reinforcement. Two variable have been considered which are the strengthening configuration of the opening region and the configuration of the dapped end reinforcement. The response has been discussed in terms several indicators including, the cracking and failure loads, maximum deflection, mode of failure, load-deflection curves, crack patterns, crack width, to recognize the optimum strengthening proposal of the opening. Results revealed that using the inclined steel bars (modified arrangement) yield better response than the conventional (standard) reinforcement (vertical stirrups) within the dapped end. For beams with pockets strengthened with crossed inclined bars, failure load enhanced in range of (8.5-11%) whereas the enhancement was in ranged in (8-10%) for the steel SFC method. Moreover, an improvement by about (11-13%) in load capacity increased when the jacketing with steel plates was applied. The maximum improvement was obtained when using the embedded rolled section within the opening with values of (21-23%).